SENIOR HIGH SCHOOL STUDENTS' THINKING AND SELF EFFICACY IN INQUIRY LEARNING - Risnanosanti, - (2010)
The problem of this research is the weakness of mathematical creative thinking ability, and students' self efficacy which is the product of teacher-centered learning process. To overcome this problem, we have to utilities models of teaching which are based on new paradigm (student-centered). One of models that can be used is inquiry learning, as this model contains a dynamic process that requires students to explore, investigate, and construct a new understanding. The aim of this research is follows: 1) compared mathematical creative thinking ability students who get inquiry learning and student who get regular learning; 2) compared self efficacy students under inquiry learning and students under regular learning. This study is quasi-experiment, involving XI th grader Senior High School in Bengkulu. The data in this study were collected from July to October 2009. The instruments used are a test of prior knowledge of mathematics, mathematical ability tests of creative thinking, self efficacy scale of the students on mathematics, and guidelines of interview. Based on the results of data analysis, it can be concluded that: 1) in general, mathematical creative thinking ability of students received inquiry learning better than students who received regular learning; 2) self efficacy of students under inquiry learning are better than students under regular learning; 3) learning model, the level of schools and students' prior knowledge of mathematics significantly affect students' ability in mathematical creative thinking; 4) there is interaction between the level of schools and learning models towards students mathematical creative thinking ability; 5) there is interaction between the levels of schools and learning models towards students self efficacy; 6) there is interaction between students prior knowledge of mathematics and learning model toward mathematical creative thinking ability; and 7) there is interaction between students prior knowledge of mathematics and learning model toward students self efficacy.